Quality of life among obese and non-obese early adolescents - Putu Vivi Paryati; I. G. Lanang Sidiartha; I. G. Ayu Trisna Windiani; I. G. A. N. Sugitha Adnyana (Paediatrica Indonesiana, 2017)
Background Obesity in adolescents adversely affects both their psychological as well as their physical health.Objective To compare the quality of life between obese and non-obese early adolescents, using the PedsQL inventory.Methods A cross-sectional study was carried out on early adolescents aged 10-12 years among several elementary schools in Denpasar, Bali. Body mass index (BMI) percentiles for age and sex were categorized as obese (BMI â‰¥95th percentile) and non-obese (BMI <95th percentile). Data on quality of life were collected using PedsQL Generic Core Scales version 4.0 inventory, filled by the children and their parents separately.Results Total PedsQL score in obese and non-obese group were significantly difference in both reports [child report: mean difference of 9.59 (95%CI 7.14 to 12.05; P<0.05) and parent-proxy report: mean difference at 8.95(95%CI6.64 to 11.26; P<0.05)]. After classifying subjects into impaired and not impaired quality of life based on a total score cut-off <78 as well as other cut-off points for each domain, the individual domains of physical, social, and school function were also significantly associated with obesity (child report: P=0.02, P< 0.001, P=0.018, respectively, and parent-proxy report:P=0.007, P<0.001, P<0.001, respectively). However, emotional function was not significantly associated with obesity (P>0.05). After adjusting for age, gender, and parental education, obesity was significantly associated with PedsQL scores in the child report (OR 7.25; 95%CI 2.94 to 17.89; P<0.05) and the parent-proxy report (OR 10.87; 95%CI 3.83 to 30.84; P<0.05).Conclusion Obese early adolescents reported significantly poorer quality of life with regards to the physical, social, school function domains and total quality of life than those who were classified into non-obese.